2017
DOI: 10.3389/fnins.2017.00429
|View full text |Cite
|
Sign up to set email alerts
|

Human Summating Potential Using Continuous Loop Averaging Deconvolution: Response Amplitudes Vary with Tone Burst Repetition Rate and Duration

Abstract: Electrocochleography (ECochG) to high repetition rate tone bursts may have advantages over ECochG to clicks with standard slow rates. Tone burst stimuli presented at a high repetition rate may enhance summating potential (SP) measurements by reducing neural contributions resulting from neural adaptation to high stimulus repetition rates. To allow for the analysis of the complex ECochG responses to high rates, we deconvolved responses using the Continuous Loop Averaging Deconvolution (CLAD) technique. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The interpretation of these results, however, is unclear because the effect has been found to depend mainly on changes of the SP, which has traditionally been thought to originate from inner hair cell receptor potentials rather than from neural elements ( Durrant, Wang, Ding, Salvi, 1998 , Eggermont, 2017 ). 2 Some recent studies, however, suggest that the SP may include neural components ( Kennedy, Kaf, Ferraro, Delgado, Lichtenhan, 2017 , Pappa, Hutson, Scott, Wilson, Fox, Masood, Giardina, Pulver, Grana, Askew, Fitzpatrick, 2019 ). The interpretation of the association between the AP/SP ratio and speech-reception thresholds thus hinges on the interpretation of the SP, which has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of these results, however, is unclear because the effect has been found to depend mainly on changes of the SP, which has traditionally been thought to originate from inner hair cell receptor potentials rather than from neural elements ( Durrant, Wang, Ding, Salvi, 1998 , Eggermont, 2017 ). 2 Some recent studies, however, suggest that the SP may include neural components ( Kennedy, Kaf, Ferraro, Delgado, Lichtenhan, 2017 , Pappa, Hutson, Scott, Wilson, Fox, Masood, Giardina, Pulver, Grana, Askew, Fitzpatrick, 2019 ). The interpretation of the association between the AP/SP ratio and speech-reception thresholds thus hinges on the interpretation of the SP, which has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…These recording techniques are supported by recent studies of the SP in human adults. Kennedy et al (2017) studied stimulus rate in amplitude of the human SP, and reported that faster repetition rates (58 to 97/s) showed higher amplitude SP compared to slower rates (7–19/s), using a filter setting similar to the present study (3–3000 Hz). The rate in the present study was intermediate, at 37/s, due to concerns about reducing Wave I and V amplitude at faster rates in newborns.…”
Section: Discussionmentioning
confidence: 75%
“…We speculate that, in addition to EPSPs, the reduction of synaptic adaptation due to synaptic loss may also contribute to larger SP ratios to very short ICIs in cochlear synaptopathy. In contrast, SP amplitudes to short stimuli were reported to be slightly reducing, because of adaptation, in normal-hearing humans as stimulus repetition rate increased 21 . Proper adaptation is important in maintaining normal hearing function because it is a fundamental principle of sensory processing that enables sensory information to be represented adequately 32 and remain robust to noise 33 .…”
Section: Discussionmentioning
confidence: 90%
“…Wave I), it may be more sensitive to synaptopathic pathology. In normal-hearing human listeners, SP amplitudes to short duration stimuli are found to be reducing as stimulus repetition rate increased 21 . In contrast, as excitatory post-synaptic potentials (EPSPs) from cochlear nerve terminals under the inner hair cells may contribute to SP 8 , the loss of a negative EPSP could enhance SP in cochlear synaptopathy.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation